2022
DOI: 10.3168/jds.2021-21728
|View full text |Cite
|
Sign up to set email alerts
|

Identification and bioactivity evaluation of flavan-3-ols in the milk of dairy sheep fed Cynomorium songaricum

Abstract: Cynomorium songaricum is a traditional medicine and also a food material that is eaten raw or processed as tea or beverages. As a featured plant in semi-desert grasslands, C. songaricum is also eaten by the cattle and sheep in the area. This research study fed dairy sheep C. songaricum to determine the flavan-3-ols in sheep milk. Catechin (Cat), epicatechin (Epi), procyanidin A1 (A1), procyanidin A2 (A2), and procyanidin B1 (B1) were detected in sheep milk with the concentration being Epi > A2 > Cat > B1 > A1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Previous study revealed that Epi, Cat, A1, A2, and B1 could enter the milk of sheep fed with C. songaricum stems (Duan et al., 2022). The present study found that these flavane‐3‐ols attenuated the recruitment of neutrophils in LPS‐treated or fin‐injured zebrafish larvae.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Previous study revealed that Epi, Cat, A1, A2, and B1 could enter the milk of sheep fed with C. songaricum stems (Duan et al., 2022). The present study found that these flavane‐3‐ols attenuated the recruitment of neutrophils in LPS‐treated or fin‐injured zebrafish larvae.…”
Section: Resultsmentioning
confidence: 97%
“…A2 was proved to be one of the extender units of the polymeric flavan‐3‐ols in C. songaricum and was speculated to be absorbed into the plasma after digestive degradation of the polymers (Duan et al., 2022). A2 and B1 have multiple peaks in the plasma concentration‐time curves, reflecting the ruminant digestion process of polymeric procyanidins in this plant.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations